ANALISA KERUSAKAN RUAS JALAN RAYA SEMARANG BOJA (Studi Kasus Pasar Jrakah – SPBU BSB) - Fikri, Fajar Ikhsanul; Rizani, Mohammad Debby; Yudaningrum, Farida (Universitas PGRI Semarang, 2024)
The dense of traffic volume resulted in road damage on the Semarang Boja highway section to be precise at KM 8 – KM 14 Semarang Boja. Overcrowding and excessive tonnage are also factors in road damage in the area. The purpose of this study was to determine the LHR on Semarang Boja highway, the effect of vehicle volume on the level of damage to Jalan Raya Semarang Boja.. This research method is quantitative. The quantitative method is a method of collecting some data with primary data, namely direct surveys in the field and secondary data needed in this study. Based on the results of the analysis, the average daily traffic (LHR) on the northbound road was 1949.57 pcu/hour and on the southbound road was 1872.83 pcu/hour classified as heavy traffic. The degree of saturation (DS) value based on traffic volume 0.75 is 6.30 in morning conditions, 2.99 in afternoon conditions, 3.77 in afternoon conditions with a very saturated category